Fostering World Peace Through ‘Cultures of Meaning’: A Case Study of Shaykh Hamdi Ben Aissa and the Sanad Collective - Omar Edaibat (Universitas Islam Negeri Sunan Kalijaga, 2018)
When considering the question of world peace, many of the political and intellectual responses of our age continue to operate within a well-defined prism that privileges secular, diplomatic, political, and economic solutions that have failed to adequately diagnose the root causes of this persistent global challenge. Further still, religion is frequently regarded as an exclusionary and divisive force, or worse still as an obstacle, that is to be channeled and contained. This paper seeks to address this imbalance. Part I seeks to provide a wider critique of the contemporary status quo and to proffer a diagnosis of the underlying root causes of our current global crises. In doing so, I build upon existing critical academic scholarship, with a special focus on Rajani Kanth’s forceful critique of ‘Euro-modernism’ and Steven D. Smith’s ‘cage’ of secular discourse. Here, I argue that the central malaise of our age relates to the shrinking landscapes of ‘meaning’ in our expanding global monoculture, a challenge that the paradigm of traditional religion is well suited to address. Part II, seeks to bolster this point further through an illustrative example of one such local communal solution in practice working from within the rich resources of Islamic spiritual tradition in my case study of Shaykh Hamdi Ben Aissa and his dynamic community, the Sanad Collective, in Eastern Canada.